Meninos e meninas digitais - Pereira, Lucas Henrique de Araújo [UNESP]; Lima, Gabriel Souza [UNESP]; Schweitzer, Christiane Marie [UNESP]; Jardim Junior, Elerson Gaetti [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The development of skills and knowledge involves a series of challenges to the teaching profession that increasingly converge in the focus of interdisciplinarity. The present work aims to make a University-society approach, working with young people from elementary school in the use of information technologies as tools of work, socializing and especially apprenticeship. Through planned actions, in accordance with the curriculum and the actors of the elementary school EE Prof. LEA Silva Moraes were developed activities with boys and girls of 7th and 8th grades of elementary school, which begin to be administrators of their careers, seeking to outline their actions for the technical vocational high school and a future college career. Through this work the fundamental concepts of logic, development of computer programs, use of computer games, interactive tools have been entered, aiding in the training of future citizens.

O desenvolvimento das habilidades e dos saberes envolve uma série de desafios ao magistério que cada vez mais converge ao foco da interdisciplinaridade. O presente trabalho tem por objetivo fazer uma aproximação universidadesociedade, trabalhando com jovens do ensino fundamental no uso de tecnologias da informação, como ferramentas de trabalho, socialização e principalmente aprendizado. Através de ações planejadas, em concordância com o currículo e os atores da escola EE Prof LEA Silva Moraes foram desenvolvidas atividades com meninos e meninas do ensino fundamental, os quais começam a serem gestores de suas carreiras, buscando delinear suas ações para o ensino médio, e uma futura carreira universitária. Neste trabalho os conceitos fundamentais de lógica, desenvolvimento de programas de computadores, uso de ferramentas interativas e jogos foram inseridos, auxiliando na formação de futuros cidadãos como agentes de transformação da sociedade, fornecendo as oportunidades de aprendizagem que uma sociedade, competitiva, atual e futura, requer.
Keywords: Education; Programming; Teaching quality; Robot; Innovation; Educational studies; Educação; Programação; Qualidade de ensino; Robô; Ferramentas interativas; Inovação; Estudos didáticos